Developing Electronic School Report (E-Rapor) for Strengthening the Profile of Pancasila Students - Amilia, Fitri; Nurkamilah, Nurkamilah; Rachman, Angraeny Unedia (Universitas Pendidikan Mandalika, 2024)
The research aims to develop an electronic school report (e-report/e-rapor) to assess the achievement of competencies profiling Pancasila students. The development of this e-report facilitated the needs of schools that did not have an assessment system for the implementation of the Enhancing Pancasila Student Profiles Project (EP4). The e-report was developed in accordance with the Decision Letter of the Education Standards, Curriculum, and Assessment Agency (BSKAP) number 009. The development of this e-report used the development method approach, commonly known as Research and Development (R&D). To test the feasibility of the developed e-report, it was evaluated based on two aspects: content validity and effectiveness. The respondents in this research were 30 teachers and/or school principals. The data analysis technique for analyzing data from the interactive e-report development process was descriptive to explain the process and the effectiveness for the product. The results of the e-report validity on the accuracy of dimensions and elements were as follows: 54% very accurate, 40% accurate, and 6% fairly accurate. Meanwhile, the accuracy of the assessment was 54% very accurate, 43% accurate, and 3% fairly accurate. The accuracy of other components was 57% very accurate, 37% accurate, and 6% fairly accurate. The e-report effectiveness on ease of use was as follows: 50% very easy, 47% easy, and 3% fairly easy. Then, the e-report attractiveness was 43% very attractive, 47% attractive, and 10% fairly attractive. The conformity of appearance with the EP4 concept was 60% very suitable, 34% suitable, and 6% fairly suitable. As a result, the e-report was recommended in assessing the implementation of EP4.